The Enemy Within: the Housekeeper in Victorian Fiction - Elisabeth Jay (Cahiers Victoriens et Edouardiens)
The introduction in the 1851 census of the new category of ‘housewife’ as distinct from the paid post of ‘housekeeper’, suggests that the Victorian cult of domesticity had created its own gendered ethical economy. This paper explores some of the ways in which the figure of the housekeeper in Victorian fiction became the site for the expression of a series of class and gender anxieties and why Victorian writers were particularly alive to the potential threat posed by a servant whose role was that of understudy.